HEREDITARY CONGENITAL FACIAL PALSY - Tariq, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Hereditary congenital facial palsy (HCFP) is a rare disorder. We report the case of 20 year old woman who presented with right sided facial weakness since her infancy. Among five generations of her family, 12 other members had facial palsy. Her detailed clinical assessment revealed no abnormality other than right sided facial paresis. A diagnosis of autosomal dominant hereditary congenital facial palsy was made.